2018
DOI: 10.3892/ol.2018.8443
|View full text |Cite
|
Sign up to set email alerts
|

miR‑204‑5p and miR‑3065‑5p exert antitumor effects on melanoma cells

Abstract: MicroRNA (miR)-204-5p was previously identified to be downregulated in melanoma compared with melanocytic nevi. This observation prompted a functional study on miR-204-5p and the newly-identified miR-3065-5p, two miRNAs suggested to be tumor-suppressive oncomiRs. Application of miR-204-5p mimics or inhibitors resulted in a decrease or increase, respectively, in melanoma cell proliferation and colony formation. miR-204-5p mimics hindered invasion, whereas miR-204-5p inhibitors stimulated cancer cell migration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 46 publications
(48 reference statements)
0
24
1
2
Order By: Relevance
“…Recent extensive studies have demonstrated that miR-204-5p exerts antitumor effects by controlling cell proliferation, apoptosis, metastasis, invasion, angiogenesis and chemotherapeutic sensitivity [22][23][24][25][26]. Zhang, B et al study uncovered that miR-204-5p expression was negatively related to the tumor TNM stage in GC [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recent extensive studies have demonstrated that miR-204-5p exerts antitumor effects by controlling cell proliferation, apoptosis, metastasis, invasion, angiogenesis and chemotherapeutic sensitivity [22][23][24][25][26]. Zhang, B et al study uncovered that miR-204-5p expression was negatively related to the tumor TNM stage in GC [17].…”
Section: Discussionmentioning
confidence: 99%
“…miR-204 was previously reported to be involved in a series of physiological and pathological processes, such as diabetic retinopathy, aortic valve disease and ulcerative disease [25][26][27]. Some recent studies revealed that miR-204-5p also exerts antitumor effects on various cancers (e.g., breast cancer, melanoma and liver cancer) through inhibiting invasion and metastasis of cancer cells [25,[28][29][30]. This study found that miR-204-5p suppressed cell viability and invasion, and regulated the expressions of E-cadherin, N-cadherin and Twist1; moreover, LOC285758 could reduce the transcription of miR-204-5p and promoted AML cell viability and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, miR-204 expression was downregulated in NPC tissues when compared with controls. A previous study revealed that miR-204 may exert antitumor effects on melanoma cells (23). miR-204 may decrease the growth, migration and invasion of colon cancer cells by deactivating the PI3K/AKT/mTOR signaling pathway and targeting C-X-C motif chemokine ligand 8 expression (24).…”
Section: Discussionmentioning
confidence: 99%